Meaning Making Over a Lifetime: A Case Study of Pat Boone - (:unkn) unknown (My University, 2022)
In the mid-1950s, Pat Boone was one of the most popular singers in America. Several years later, Boone’s mass appeal as a star had begun to diminish and he was left without an obvious fanbase. Yet, today 60 years later, Boone is the star of several television ads, has appeared on one of the biggest shows on television, and has recently had a song explode to over five million views on social media. In order for Boone to achieve the continued fame he enjoys today, Boone has shapeshifted his celebrity to cater to receptive audiences. Using Boone as a case study, this study explores how stars engage in meaning making to cater to different audience bases. By closely tracking and analyzing the path of Boone’s celebrity, we better understand how stars come into positions of power and maintain influence over society.
Keywords: Celebrity Case Study; Celebrity formation; Celebrity meaning making; Celebrity studies; Changing Celebrity; Pat Boone